Colonial Labor in Twentieth-Century Angola - Ball, Jeremy A. (History compass, 2005)
For most of the twentieth century, Portuguese colonial rule in Angola relied on forced labor. The state acted as labor recruiter and ensured private enterprise a reliable supply of migrant workers. The line between coerced and voluntary labor was often an ambiguous one, though it is clear that slavery existed as late as the 1910s and that a migrant labor system without any coercion only emerged in the 1960s. Unfortunately, African slaves and forced laborers did not write about their experiences. We are fortunate, however, to have glimpses of how workers experienced labor in the form of several investigative reports. Angola differed from neighboring British and French colonies in central and southern Africa only in the extent to which colonial authorities relied on forced labor.